Alleviation of salinity stress in rice genotypes using growth regulators - Misratia, Khadija Mohamed (2015)
Salinity is a major problem of rice especially the salt sensitive cultivars in the granary areas. This problem consequently reduces the potential acreage for the production of the crop. To solve this problem, the present study was conducted to determine how growth regulators (GA3 and kinetin) could be explored to alleviate salinity stress in different rice cultivars. Under laboratory condition, exogenous applications of 150 ppm GA3 and 15 ppm kinetin on six rice cultivars (MR185, MR211, MR219, MR220, MR232 and Pokkali as check) were used to alleviate salinity stress of the crop at different salinity levels (0, 50, 100, 150 and 200 Mm NaCl). It was found that higher salinity levels (150 and 200 mM) reduced seed germination, shoot length, root length, vigour index, fresh weight, dry weight, relative water content, soluble sugar, soluble protein, free proline, K+, Ca2+, Mg2+ in rice seedlings. However, these parameters were mildly affected in plants grown at lower salinity levels (50 and 100 mM NaCl). Application of 150 ppm GA3 alleviated salinity stress in all the cultivars and thus improved all the traits measured. With application of 150ppm GA3, Pokkali and MR219 tolerated salinity stress better than the rest tested cultivars. Application of 150ppm GA3 was chosen for its better performance and used for improvement of morphological, physiological and yield traits of Pokkali and MR219 under glass house condition at different salinity levels (0, 50, 100, 150 and 200 mM NaCl). All the studied morphological traits (plant height, tillers plant-1, leaves plant-1, leaf length, plant fresh and dry weight) and physiological attributes (chlorophyll a, b, and total chlorophyll contents, photosynthetic rates, stomatal conductance, transpiration rate,) were severely affected at higher salinity levels ( 150 and 200 mM). Application of 150ppm GA3 consistently improved the salinity tolerance of the two cultivars morphologically and physiologically at mild salinity levels (0-100 mM NaCl). Higher salinity levels (150 and 200 mM) severely and significantly (P≤ 0.05) affected the tested cultivars and it resulted in tiller sterility. Beyond this level, application of 150ppm GA3 could not alleviate the salinity stress imposed. However, at mild salinity levels (50 and 100mM NaCl), there was production of panicle but panicle length, filled grains per panicle, weight of filled grains, seed index, harvest index, and grain yield per pot were all significantly reduced (P≤ 0.05) with increase in the number and weight of unfilled grains and spikelets. Finally, 150 ppm GA3 was used to improve biochemical and ionic changes, enzymatic activities and expression profile of OsLEA gene in MR219 and Pokkali under moderate salinity (100 mM). Under this salinity level, there was significant increase in concentrations of soluble sugar, soluble proteins and free proline in both MR219 and Pokkali cultivars at P≤ 0.05. With GA3 application, salinity stress was less alleviated and biochemical changes were less stabilized. For the ionic contents, there was high Na+ content while K+, Ca2+ and Mg2+ were low in concentration in the two cultivars in the control. However, with the application of GA3 at moderate salinity(100mM NaCl), there was decrease in Na+ level while K+, Ca2+ and Mg2+ increased. For enzymatic activities, peroxides, Catalase and Ascorbate peroxides were significantly (P≤ 0.05) high in the control. Under salinity stress, GA3 treatment improved the enzymatic activities above the control (zero GA3 application) at P≤ 0.05. In Semi quantitative analysis for OsLEA gene expression, there was no distinction between the gene bands of the control and the salinity stressed plants in MR219. However, when GA3 was applied to the plants, there was clear distinction between the gene bands of control and salinity stressed plants. For expression of OsLEA genes in Pokkali, the were band differences among the control plants and plants treated with GA3. The expression level of OsLEA gene in Pokkali was also different. Based on the results of the present investigations, it may be concluded that MR219 (indigenous) and Pokkali (exotic) rice cultivars can be produced in moderately saline soils with the application of 150 ppm GA3.